Measuring the English Competency of Engineering Students through the English Proficiency Test (EPT) and the Translation Quality Assessment - Alief Sutantohadi; Yulius Harry Widodo (Humaniora Scientia, 2018)
This descriptive qualitative research is conducted to know the students’ competency in Englishthrough their achievements in English Proficiency Test (EPT) and the translation qualityassessment result. The data from EPT achievement scores were analyzed statistically byconsidering the lowest, average and highest scores. While the data from the translation resultwere analyzed with translation approach by using translation assessment instrument and theContent Analysis method by Spradley.  The results of the analysis shows that most of the data 83data (55 %) were translated accurately, there are 49 data (33%) are considered as less accuratetranslation and the rest, there are 18 data (12 %) are considered as inaccurate translation.Moreover, from acceptability assessment most of the sentences of the target text 80 data (53%)are evaluated as acceptable, there are 51 data (34 %) in this research that are considered asless acceptable and the rest 19 data (13%) in this research that are considered as unacceptabletranslation. Although most of the data are accurate and acceptable, it cannot be inferred that thetranslation of the abstract by the students of engineering field is high-quality. The reason isbecause there are still many data that are less accurate and less acceptable if it is seen from thetransfer of the source text content. This condition reflects the translation competence of thestudent is fair and need to practice more in translating different kind of texts to improve theirtranslation competency.